ONLINE LEARNING: DINAMIKA PEMBELAJARAN SELAMA PANDEMI DALAM PERSEPSI MAHASISWA - Pangestu Gusti Putri; Idris Idris (Jurnal Pendidikan Ilmu Sosial, 2022)
The emergence of covid-19 outbreak has an impact on implementing virtual learning. This transformation has become one of the concerns for students, so the process of ongoing learning has a decrease in quality. Need information from student’s perceptions of how the learning process they expect. This study aims to analyze student perceptions of online learning. This study uses a quantitative approach with a survey method which is analyzed using statistical-descriptive analysis techniques. Collecting data in the form of a questionnaire distributed to 112 active students of the S1 Social Studies Program, Faculty of Social Sciences, State University of Malang. The results showed that online learning is still considered less effective by looking at the carrying capacity of perceptions both on internal and external factors. The conclusion based on the results of this study is the response of students' perceptions of online learning, it is necessary to fulfill student needs for online learning such as facilities, media, methods, and assignment allocation systems that need to be improved and provided by education stakeholders.